Dose-dependent long-term effects of a single radiation event on behaviour and glial cells. (1st February 2021) - Ung, Marie-Claire; Garrett, Lillian; Dalke, Claudia; Leitner, Valentin; Dragosa, Daniel; Hladik, Daniela; Neff, Frauke; Wagner, Florian; Zitzelsberger, Horst; Miller, Gregor; de Angelis, Martin Hrabĕ; Rößler, Ute; et al.
Abstract: Purpose: The increasing use of low-dose ionizing radiation in medicine requires a systematic study of its long-term effects on the brain, behaviour and its possible association with neurodegenerative disease vulnerability. Therefore, we analysed the long-term effects of a single low-dose irradiation exposure at 10 weeks of age compared to medium and higher doses on locomotor, emotion-related and sensorimotor behaviour in mice as well as on hippocampal glial cell populations. Materials and methods: We determined the influence of radiation dose (0, 0.063, 0.125 or 0.5 Gy), time post-irradiation (4, 12 and 18 months p.i.), sex and genotype (wild type versus mice with Ercc2 DNA repair gene point mutation) on behaviour. Results: The high dose (0.5 Gy) had early-onset adverse effects at 4 months p.i. on sensorimotor recruitment and late-onset negative locomotor effects at 12 and 18 months p.i. Notably, the low dose (0.063 Gy) produced no early effects but subtle late-onset (18 months) protective effects on sensorimotor recruitment and exploratory behaviour. Quantification and morphological characterization of the microglial and the astrocytic cells of the dentate gyrus 24 months p.i. indicated heightened immune activity after high dose irradiation (0.125 and 0.5 Gy) while conversely, low dose (0.063 Gy) induced more neuroprotective features. Conclusion: This is one of the first studies demonstrating such long-term and late-onset effects on brain and behaviour after a single radiation event in adulthood.